Preparation method of low-loss amorphous nanocrystalline shielding sheet

Through double-sided magnetic crushing technology, the amorphous nanocrystalline soft magnetic alloy strip is synchronously fragmented. Combined with regular patterns and irregular point crushing, the problems of low efficiency and performance differences in the existing technology are solved, and high magnetic field is achieved Preparation of amorphous nanocrystal shielding sheets with conductivity and low loss.

CN119212360APending Publication Date: 2024-12-27NINGBO ZHONGKE BIPULASI NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411543916.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

When preparing amorphous nanocrystal shielding sheets, the existing magnetic crushing process is difficult to meet the requirements of low loss and high magnetic permeability at the same time, and the production efficiency is low and the performance differences fluctuate greatly.

Method used

The double-sided magnetic crushing method is used to synchronous fragmentation of amorphous nanocrystalline soft magnetic alloy strips, and the regular pattern crushing and irregular point crushing are used respectively. The pressure treatment of the double-sided magnetic crushing rollers makes the strips appear macroscopic Regular patterns and micro irregular fragmented states, and enhance bonding and insulation effects through heating and filling of double-sided adhesive.

Benefits of technology

Improve production efficiency, meet the requirements of high magnetic permeability and low loss, and prepare high-performance amorphous nanocrystal shielding sheets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119212360A_ABST
    Figure CN119212360A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a low-loss amorphous nanocrystalline shielding sheet, which comprises the following steps of: laminating an amorphous nanocrystalline soft magnetic alloy strip subjected to heat treatment with a double faced adhesive tape to obtain a glue-coated soft magnetic composite strip; performing double-sided fragmentation treatment on the rubber-coated soft magnetic composite strip to obtain a double-sided fragmented magnetic strip; wherein the double-sided fragmentation treatment comprises the step of carrying out synchronous fragmentation treatment on the two sides of the rubber-coated soft magnetic composite strip by adopting a first magnetic fragmentation mode and a second magnetic fragmentation mode respectively; the second magnetic fragmentation mode is different from the first magnetic fragmentation mode, so that the double-sided magnetic fragmentation strip presents a macroscopic regular pattern and a microscopic irregular fragmentation state; and laminating and cutting the multiple layers of double-sided crushed magnetic tape materials to obtain the amorphous nanocrystalline shielding sheet. The method has the beneficial effects that the magnetically soft alloy strip subjected to magnetic crushing shows regular patterns macroscopically, and irregular fragments appear in the patterns, so that the finally prepared shielding sheet can meet the requirements of high magnetic conductivity and low loss at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of shielding sheet preparation, and in particular to a method for preparing a low-loss amorphous nanocrystalline shielding sheet. Background Art

[0002] With the rapid development of wireless charging technology, wireless charging products have been rapidly popularized, which in turn has put forward higher and higher requirements for the technical development of the wireless charging industry. The amorphous nanocrystalline shielding film in the wireless charging module is one of the main components that affect the performance of the wireless product module. The processing and preparation technology of the shielding film is also the focus of the current development of the wireless charging field.

[0003] Amorphous nanocrystalline shielding sheets are usually made of amorphous nanocrystalline strips as core raw materials, and are prepared through processes such as strip heat treatment - glue coating - crushed magnets - multi-layer bonding - die cutting. Among them, the "crushed magnets" process is a key process that determines the main properties of the shielding sheet, such as magnetic permeability, loss, anti-saturation, and temperature rise. "Crushed magnets" means fragmenting the heat-treated amorphous nanocrystalline strips, dividing the entire amorphous nanocrystalline strip into small units to introduce air gaps, so that the amorphous nanocrystalline shielding sheet reaches the required magnetic permeability level, improves the anti-saturation of the wireless charging module, and at the same time, greatly reduces the eddy current loss generated during wireless charging, thereby improving the charging efficiency.

[0004] The existing magnetic crushing process can meet the basic needs to a certain extent, but there are still certain problems and limitations: the traditional magnetic crushing process can usually only break the shielding sheet into irregular cracks, and the shielding sheet prepared in this way generally has high loss; some processes can achieve regular patterned magnetic crushing. Although it can achieve the goal of low loss, its production efficiency is low and it is difficult to meet the requirements of high magnetic permeability. It is necessary to increase the number of shielding sheet layers to meet the requirements of high magnetic permeability; there are also a few processes that first perform patterned magnetic crushing and then crushing magnetic crushing. There is also the problem of low production efficiency, and it cannot be guaranteed that the crushing roller will completely crush in the middle of the patterned magnetic crushing, and its performance differences fluctuate greatly. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for preparing a low-loss amorphous nanocrystalline shielding sheet.

[0006] The technical problem solved by the present invention can be achieved by adopting the following technical solutions:

[0007] A method for preparing a low-loss amorphous nanocrystalline shielding sheet, comprising:

[0008] The heat-treated amorphous nanocrystalline soft magnetic alloy strip is laminated with a double-sided adhesive to obtain an adhesive-coated soft magnetic composite strip;

[0009] The rubber-coated soft magnetic composite tape is subjected to double-sided fragmentation processing to obtain a double-sided shredded magnetic tape material; wherein the double-sided fragmentation processing comprises respectively using a first shredding method and a second shredding method to perform synchronous fragmentation processing on both sides of the rubber-coated soft magnetic composite tape; the first shredding method is regular pattern shredding, and the second shredding method is irregular point shredding, so that the double-sided shredded magnetic tape material presents a macroscopic regular pattern and a microscopic irregular fragment state;

[0010] The multi-layer double-sided shredded magnetic tape is laminated and cut to obtain an amorphous nanocrystalline shielding sheet.

[0011] Preferably, the double-sided fragmentation process is to roll the rubber-coated soft magnetic composite strip through at least one pair of opposing crushed magnetic rollers; the opposing crushed magnetic rollers have opposite rotation directions and the same surface linear speed.

[0012] Preferably, the opposing pressed magnetic crushing rollers have one magnetic crushing roller with a regular magnetic crushing pattern on its surface for completing the regular pattern magnetic crushing; and the other magnetic crushing roller has convex magnetic crushing dots on its surface for completing the irregular point crushing.

[0013] Preferably, the irregular point-type crushing includes convex point-type crushed magnets.

[0014] Preferably, the arrangement of the pattern of the regular patterned broken magnetic pieces is consistent with the arrangement of the convex points of the convex point type broken magnetic pieces, and the convex points correspond one to one with the inside of the pattern.

[0015] Preferably, the line speed is 10 m / min to 50 m / min.

[0016] Preferably, before the double-sided fragmentation treatment, a protective film is applied to the side of the adhesive-coated soft magnetic composite strip that is not bonded with the double-sided adhesive.

[0017] After the double-sided fragmentation process is completed, the protective film is removed.

[0018] Preferably, before and during the double-sided fragmentation process, the method further comprises: heating the rubber-coated soft magnetic composite strip;

[0019] The heating temperature of the heating treatment is 40°C to 80°C.

[0020] Preferably, the double-sided adhesive in the adhesive-coated soft magnetic composite strip is in a molten state with fluidity;

[0021] During the double-sided shredding process, the double-sided adhesive in a molten state is filled into the shredded gaps of the double-sided shredded tape material.

[0022] Preferably, the double-sided fragmentation process is performed at least once continuously.

[0023] The advantages or beneficial effects of the technical solution of the present invention are:

[0024] The present invention adopts a double-sided magnetic fragmentation method to perform synchronous fragmentation processing on the soft magnetic alloy strip, thereby improving the overall production efficiency; at the same time, different methods are used to fragment the two sides, so that the soft magnetic alloy strip after magnetic fragmentation presents a regular pattern at a macroscopic level, while irregular fragments appear inside the pattern, so that the finally prepared shielding sheet can meet the requirements of magnetic permeability and lower loss at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A schematic diagram of a magnetic fragmentation method of a low-loss amorphous nanocrystalline shielding sheet in a preferred embodiment of the present invention;

[0026] Figure 2 A schematic diagram of a patterned crushed magnetic roller surface in a preferred embodiment of the present invention;

[0027] Figure 3 This is a partial enlarged view of the patterned magnetic crushing roller A in a preferred embodiment of the present invention;

[0028] Figure 4 It is a schematic diagram of the roller surface of the convex point type crushed magnetic roller in a preferred embodiment of the present invention;

[0029] Figure 5 It is a partial enlarged view of the convex point type magnetic crushing roller B in a preferred embodiment of the present invention;

[0030] Figure 6 This is a rendering of the surface of a soft magnetic alloy strip after double-sided magnetic crushing in a preferred embodiment of the present invention.

[0031] Description of reference numerals:

[0032] 1. Patterned crushed magnetic roller; 11. Pattern; 2. Bump-type crushed magnetic roller; 21. Bump; 3. Glue-coated soft magnetic composite strip. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0035] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but they are not intended to limit the present invention.

[0036] See also Figures 1 to 6 In a preferred embodiment of the present invention, based on the above problems existing in the prior art, a method for preparing a low-loss amorphous nanocrystalline shielding sheet is provided, comprising:

[0037] S100, laminating the heat-treated amorphous nanocrystalline soft magnetic alloy strip with a double-sided adhesive to obtain an adhesive-coated soft magnetic composite strip;

[0038] The selected amorphous nanocrystalline soft magnetic alloy strip is heat treated. The heat treatment can promote the growth, refinement or change of shape of the grains inside the alloy, adjust the grain size distribution, so as to reduce the hysteresis loss and eddy current loss, and improve the magnetic permeability and saturation magnetization. At the same time, the heat treatment can also eliminate the stress generated by the amorphous nanocrystalline soft magnetic alloy strip during the pre-processing process, and reduce the risk of magnetic instability or material failure caused by stress.

[0039] After the amorphous nanocrystalline soft magnetic alloy strip is heat treated, a double-sided adhesive tape is pasted on one side of the heat-treated amorphous nanocrystalline soft magnetic alloy strip, and a release film on the non-pasting side of the double-sided adhesive tape is retained.

[0040] As a preferred embodiment, before and during the double-sided fragmentation process, the method further includes: heating the rubber-coated soft magnetic composite strip; the heating temperature is preferably 40°C to 80°C.

[0041] As a preferred embodiment, the double-sided adhesive in the adhesive-coated soft magnetic composite strip is in a molten state with fluidity;

[0042] During the double-sided shredding process, the molten double-sided adhesive fills the gaps between the shredded double-sided tape materials.

[0043] Specifically, by attaching double-sided tape on the surface of the soft magnetic alloy strip, the soft magnetic alloy strip can still maintain its original integrity after being broken.

[0044] At the same time, the double-sided tape in the molten state has a certain fluidity, so that during the magnetic crushing process, the double-sided tape can flow into and fill the gaps between the fragments, playing a role of insulation and isolation.

[0045] Furthermore, the rubber-coated soft magnetic composite strip is heated before and during the double-sided fragmentation process to change the colloidal fluidity of the double-sided adhesive bonded to the surface of the rubber-coated soft magnetic composite strip, so that it can be more fully filled in the gaps of the fragments after the magnetic fragmentation.

[0046] After cooling to room temperature, the double-sided adhesive is completely cured to form a stable bonding and insulation structure, ensuring that the fragmented strip maintains the required magnetic properties while achieving good electrical isolation.

[0047] As a preferred embodiment, before the double-sided fragmentation process, a protective film is applied to the side of the adhesive-coated soft magnetic composite strip that is not bonded with the double-sided adhesive.

[0048] After the double-sided fragmentation process is completed, the protective film is removed.

[0049] Specifically, during the fragmentation process, a protective film is required on the side of the soft magnetic alloy strip that is not attached with the double-sided adhesive. By providing the protective film, the soft magnetic alloy strip can be effectively isolated from direct contact with the magnetic fragmentation equipment (such as magnetic fragmentation rollers), preventing the introduction of impurities or unnecessary scratches during the magnetic fragmentation process, and ensuring that the purity and performance of the final shielding sheet are not damaged.

[0050] After the subsequent fragmentation process is completed, the protective film is removed.

[0051] S200, performing double-sided fragmentation processing on the rubber-coated soft magnetic composite strip to obtain a double-sided shredded magnetic strip; wherein the double-sided fragmentation processing includes respectively performing synchronous fragmentation processing on both sides of the rubber-coated soft magnetic composite strip by using a first shredding method and a second shredding method; the first shredding method is regular pattern shredding, and the second shredding method is irregular point shredding, so that the double-sided shredded magnetic strip presents a macroscopic regular pattern and a microscopic irregular fragment state;

[0052] Specifically, regular patterned magnetic fragments and irregular dot-type magnetic fragments are used to synchronously fragment the front and back sides of the soft magnetic alloy strip with double-sided adhesive, so as to achieve double-sided fragmentation processing.

[0053] As a preferred embodiment, the double-sided fragmentation process is to roll the rubber-coated soft magnetic composite strip through at least one pair of opposing crushed magnetic rollers; the opposing crushed magnetic rollers have opposite directions of rotation and the same surface linear speed.

[0054] As a preferred embodiment, among the pressed magnetic crushing rollers, one of the magnetic crushing rollers has a regular magnetic crushing pattern on its surface for completing regular pattern magnetic crushing; and the other magnetic crushing roller has convex points on its surface for completing irregular point crushing.

[0055] As a preferred embodiment, the irregular point-type crushed magnetic particles include convex point-type crushed magnetic particles.

[0056] Further, such as Figure 2 and Figure 3 As shown, the regular patterned crushed magnets use a patterned crushed magnet roller 1; Figure 4 and Figure 5 As shown, the irregular dot-type crushed magnets use a convex dot-type crushed magnet roller 2.

[0057] As a preferred embodiment, wherein Figure 6 As shown, the arrangement of the pattern 11 of the regular patterned broken magnetic pieces is consistent with the arrangement of the bumps 21 of the bump-type broken magnetic pieces, and the bumps 21 correspond one-to-one to the inside of the pattern 11.

[0058] Specifically, the arrangement of the patterns 11 on the patterned crushed magnetic roller 1 is consistent with the arrangement of the convex points 21 on the convex point type crushed magnetic roller 2 , and the convex points 21 correspond to the inside of the patterns 11 one by one.

[0059] Furthermore, by adjusting the spacing between the patterned crushed magnetic roller 1 and the convex point crushed magnetic roller 2 and the relative positions of the pattern 11 and the convex point 21, each pattern 11 on the bonding surface of the patterned crushed magnetic roller 1 and the soft magnetic alloy strip has a corresponding convex point 21 on the convex point crushed magnetic roller 2 on the opposite side, and the corresponding patterns 11 and convex points 21 are respectively located on the front and back sides of the soft magnetic alloy strip, and then the front and back sides of the glue-coated soft magnetic composite strip are synchronously fragmented together to obtain a double-sided crushed magnetic tape material.

[0060] Furthermore, each pattern 11 on the patterned crushed magnetic roller 1 may be a triangle, a rectangle or other polygon, or a combination of these shapes.

[0061] The regular pattern crushing is equivalent to the cutting process of the strip. The edge of the pattern 11 is equivalent to the cutting edge, and the inner area surrounded by the edge is concave; each convex point 21 on the convex point crushing roller 2 can just fit into the concave area of ​​the corresponding pattern 11.

[0062] Assuming that the pattern 11 is a rectangle, each edge of the matrix pattern is equivalent to a cutting edge, and the inner area formed by the edges is concave. Figure 6 As shown, the convex points 21 correspond to the patterns 11 one by one, and each convex point 21 is located in a concave area of ​​the corresponding pattern 11 .

[0063] Furthermore, the linear speeds of the first magnetization breaking method and the second magnetization breaking method are the same.

[0064] Specifically, the line speeds of the patterned magnet crushing roller and the convex point magnet crushing roller are consistent, so that during the magnet crushing process, each pattern 11 has a corresponding convex point 21 inside, ensuring the consistency of magnet crushing in each area.

[0065] As a preferred embodiment, the line speed is 10 m / min to 50 m / min.

[0066] As a preferred embodiment, the double-sided fragmentation process is performed at least once continuously.

[0067] S300, stacking and cutting multiple layers of double-sided shredded magnetic tape materials to obtain an amorphous nanocrystalline shielding sheet.

[0068] Specifically, a plurality of groups of double-sided shredded magnetic tapes are selected for lamination and bonding to obtain a semi-finished shielding sheet; then, the semi-finished shielding sheet is cut according to a preset size and a preset shape to finally obtain an amorphous nanocrystalline shielding sheet.

[0069] It should be noted that the number of stacked layers, cutting size, and cutting shape in the shielding sheet can be set according to actual needs, and the present invention does not limit this.

[0070] Specifically, the existing magnetic fragmentation method of using the same pattern or bumps on both sides, or using patterning first and then bumping, cannot meet the requirements of low loss and high magnetic permeability at the same time, and has low production efficiency. The preparation method of the present invention laminates the heat-treated soft magnetic alloy strip with double-sided adhesive, and performs double-sided fragmentation treatment on the soft magnetic alloy strip with double-sided adhesive, and then laminates and cuts multiple double-sided fragmented soft magnetic alloy strips to finally obtain an amorphous nanocrystalline shielding sheet. During the preparation process, the soft magnetic alloy strip is fragmented by adopting a double-sided synchronous crushing method, which helps to improve the overall production efficiency. In addition, the two sides use crushing rollers with different patterns (patterned + convex point type), and the convex points of the convex point type crushing roller correspond one by one to the pattern inside the patterned crushing roller, so that the soft magnetic alloy strip after crushing presents a regular pattern at the macro level, and irregular fragments inside the pattern, so that the finally prepared shielding sheet can meet the requirements of high magnetic permeability and low loss at the same time, thereby preparing a high-performance amorphous nanocrystalline shielding sheet.

[0071] The following examples and comparative examples are provided to further illustrate and describe the preparation method of the present invention:

[0072] Embodiment 1

[0073] In this embodiment 1, a Fe-Si-B-Nb-Cu nanocrystalline soft magnetic alloy strip with a thickness of 20 μm is selected as the raw material for crushed magnets, and the preparation method of the present invention is used to crush the magnets, and the crushed magnet strips are bonded into a 4-layer structure to obtain the final shielding sheet. Specifically, the following steps are included:

[0074] S100A, a double-sided adhesive is applied to one side of the heat-treated nanocrystalline soft magnetic alloy strip, while retaining the release film on the non-adhering side of the double-sided adhesive, to obtain a combination of the nanocrystalline soft magnetic alloy strip and the double-sided adhesive, i.e., an adhesive-coated soft magnetic composite strip;

[0075] S200A, adjusting the relative positions of the pattern on the patterned crushing roller 1 and the convex points on the convex crushing roller 2 so that the inside of the pattern corresponds to the convex points one by one, and then adjusting the spacing between the patterned crushing roller 1 and the convex crushing roller 2 according to the thickness of the nanocrystalline strip, preheating the combination of the nanocrystalline strip and the double-sided tape before crushing, and then starting the patterned crushing roller 1 and the convex crushing roller 2 and keeping the linear speeds of the two consistent, and fragmenting the combination of the nanocrystalline strip and the double-sided tape to obtain the double-sided crushed magnetic tape after crushing;

[0076] The preheating temperature is 50° C., and the linear speeds of the patterned crushed magnetic roller 1 and the convex point crushed magnetic roller 2 are both 30 m / min.

[0077] S300A, select 4 groups of nanocrystalline strips after crushing magnets for lamination and bonding to obtain a semi-finished shielding sheet; then, cut the semi-finished shielding sheet according to a preset size and shape to finally obtain a shielding sheet.

[0078] In this embodiment, the shielding sheet is cut into a circular ring structure with specifications of 19.9 mm (outer diameter)×8.8 mm (inner diameter) for the convenience of testing.

[0079] Several groups of shielding sheets prepared by the above method were selected for testing, and their average magnetic permeability and average magnetic loss value at 100kHz were tested using an impedance analyzer; then, a coil with a primary and secondary turns ratio of N1:N2=40:20 turns was wound on the annular shielding sheet, and its average loss value at 100kHz / 200mT was tested using an AC BH meter. The specific test results are shown in Tables 1 and 2 below.

[0080] Embodiment 2

[0081] In this embodiment, a soft magnetic alloy strip of the same specifications as in the first embodiment is selected, and the double-sided fragmentation process of step S200A is repeated twice. The rest of the preparation methods, parameters, specifications and dimensions are the same as in the first embodiment.

[0082] The same testing method as that of Example 1 was used to perform a performance test on the shielding sheet prepared in Example 2. The specific test results are shown in Table 1.

[0083] Comparative Example 1

[0084] This comparative example uses a soft magnetic alloy strip of the same specifications as in Example 1, but uses two patterned magnetic crushing rollers 1 to simultaneously fragment the soft magnetic alloy strip, and the rest of the preparation method, parameters, specifications and dimensions are the same as in Example 1. Specifically, the following steps are included:

[0085] S100B, as S100A in the first embodiment.

[0086] S200B, using two patterned crushing rollers 1 with the same pattern as that in the first embodiment to synchronously fragment the combination of the nanocrystalline ribbon and the double-sided tape.

[0087] The patterns of the two crushed magnet rollers and the assembly overlap each other, and the adjustment method and spacing of the crushed magnet rollers are the same as those in the first embodiment; the assembly of the nanocrystalline ribbon and the double-sided adhesive tape is preheated before crushing;

[0088] The preheating temperature and the linear speed of the magnetic crushing roller are the same as those in the first embodiment.

[0089] S300B, as S300A in the first embodiment.

[0090] The same testing method as that of Example 1 was used to perform a performance test on the shielding sheet prepared in Comparative Example 1. The specific test results are shown in Table 2.

[0091] Comparative Example 2

[0092] This comparative example uses the same soft magnetic alloy strip as in Example 1, but uses two convex magnetic crushing rollers 2 to simultaneously fragment the soft magnetic alloy strip, and the rest of the preparation method, parameters, specifications and dimensions are the same as in Example 1. Specifically, the following steps are included:

[0093] S100C, as S100A in the first embodiment.

[0094] S200C, using two convex point crushing rollers 2 of the same specifications as those in the first embodiment to synchronously fragment the combination of the nanocrystalline ribbon and the double-sided adhesive.

[0095] Among them, the patterns of the two crushed magnetic rollers when they are attached to the assembly overlap up and down, and the adjustment method and spacing of the crushed magnetic rollers are the same as those in Example 1; the assembly of the nanocrystalline strip and the double-sided tape is preheated before crushing the magnets; the preheating temperature and the linear speed of the crushed magnetic rollers are the same as those in Example 1.

[0096] S300C, as S300A in the first embodiment.

[0097] The same testing method as that of Example 1 was used to perform a performance test on the shielding sheet prepared in Comparative Example 2. The specific test results are shown in Table 2.

[0098] Comparative Example 3

[0099] This comparative example uses a soft magnetic alloy strip of the same specifications as in Example 1, but uses a conventional single-sided magnetic fragmentation process, and the soft magnetic alloy strip is fragmented twice by a patterned magnetic fragmentation roller 1 and a convex point magnetic fragmentation roller 2, respectively. The remaining preparation methods, parameters, specifications and dimensions are the same as in Example 1. Specifically, the following steps are included:

[0100] S100D, as S100A in the first embodiment.

[0101] S200D, use a patterned magnetic crushing roller 1 with the same pattern as in Example 1 to perform a first fragmentation process on the combination of nanocrystalline strip and double-sided tape, and then use a convex magnetic crushing roller 2 with the same specifications as in Example 1 to perform a second fragmentation process on the combination after the first magnetic crushing.

[0102] The crushing roller on the other side is replaced by a flat roller with a smooth roller surface; the combination of the nanocrystalline strip and the double-sided tape is preheated before crushing; the preheating temperature and the linear speed of the crushing roller are the same as those in Example 1.

[0103] S300D, as S300A in the first embodiment.

[0104] The same testing method as that of Example 1 was used to perform a performance test on the shielding sheet prepared in Comparative Example 3. The specific test results are shown in Table 2.

[0105] Table 1 Performance parameters of shielding sheets of embodiment 1 and embodiment 2

[0106]

[0107] The above Table 1 shows the difference in the shielding sheet preparation process between Example 1 and Example 2, as well as the average magnetic permeability, average loss value and average magnetic loss of the shielding sheet finally obtained. It can be seen that to achieve the same target magnetic permeability (the target magnetic permeability is set to 3000 in this embodiment), with the increase of the number of magnetic crushing, the average loss and average magnetic loss of the shielding sheet can be further reduced. Therefore, according to the shielding sheets of different specifications, the appropriate number of magnetic crushing is selected, which helps to further improve the comprehensive performance of the shielding sheet while obtaining the target magnetic permeability.

[0108] Table 2 Performance parameters of shielding sheets of Example 1 and Comparative Examples 1, 2, and 3

[0109]

[0110] The above Table 2 shows the differences in the shielding sheet preparation process between Example 1 and Comparative Examples 1 to 3, as well as the average magnetic permeability and average loss value of the shielding sheet finally obtained. It can be seen that the shielding sheet prepared by synchronously crushing the soft magnetic alloy strip using the crushing rollers (patterned + convex point type) with different patterns of the present invention has lower losses when obtaining the same target magnetic permeability value compared to the traditional preparation process. At the same time, the crushing process of the present invention only needs to perform one crushing process to achieve the same or even better fragmentation degree as the existing process. The process is simpler and more convenient, and the prepared shielding sheet has better comprehensive performance.

[0111] The advantages or beneficial effects of adopting the above technical solution are: the present invention adopts a double-sided magnetic fragmentation method to perform synchronous fragmentation processing on the soft magnetic alloy strip, thereby improving the overall production efficiency; at the same time, different methods are used to fragment the two sides, so that the soft magnetic alloy strip after magnetic fragmentation presents a regular pattern at a macroscopic level, while irregular fragments appear inside the pattern, so that the finally prepared shielding sheet can meet the requirements of high magnetic permeability and low loss at the same time.

[0112] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the contents of this specification and illustrations should be included in the protection scope of the present invention.

Claims

1. A method for preparing a low-loss amorphous nanocrystalline shielding sheet, characterized in that: include: The heat-treated amorphous nanocrystalline soft magnetic alloy strip is laminated with a double-sided adhesive to obtain an adhesive-coated soft magnetic composite strip; The rubber-coated soft magnetic composite tape is subjected to double-sided fragmentation processing to obtain a double-sided shredded magnetic tape material; wherein the double-sided fragmentation processing comprises respectively using a first shredding method and a second shredding method to perform synchronous fragmentation processing on both sides of the rubber-coated soft magnetic composite tape; the first shredding method is regular pattern shredding, and the second shredding method is irregular point shredding, so that the double-sided shredded magnetic tape material presents a macroscopic regular pattern and a microscopic irregular fragment state; The multi-layer double-sided shredded magnetic tape is laminated and cut to obtain an amorphous nanocrystalline shielding sheet.

2. The method for preparing the amorphous nanocrystalline shielding sheet according to claim 1, characterized in that: The double-sided fragmentation process is to roll the rubber-coated soft magnetic composite strip through at least one pair of opposing crushed magnetic rollers; the opposing crushed magnetic rollers have opposite rotation directions and the same surface linear speed.

3. The method for preparing the amorphous nanocrystalline shielding sheet according to claim 2, characterized in that: The opposing pressed magnetic crushing rollers have one magnetic crushing roller with a regular magnetic crushing pattern on its surface for completing the regular pattern magnetic crushing; and the other magnetic crushing roller has a magnetic crushing convex point on its surface for completing the irregular point crushing.

4. The method for preparing the amorphous nanocrystalline shielding sheet according to claim 1, characterized in that: The irregular point-type crushing includes convex point-type crushed magnets.

5. The method for preparing the amorphous nanocrystalline shielding sheet according to claim 4, characterized in that: The arrangement of the pattern of the regular pattern broken magnetic pieces is consistent with the arrangement of the convex points of the convex point type broken magnetic pieces, and the convex points correspond one to one with the inside of the pattern.

6. The method for preparing the amorphous nanocrystalline shielding sheet according to claim 2, characterized in that: The line speed is 10m / min to 50m / min.

7. The method for preparing the amorphous nanocrystalline shielding sheet according to claim 1, characterized in that: Before the double-sided fragmentation treatment, a protective film is applied to the side of the adhesive-coated soft magnetic composite strip that is not bonded with the double-sided adhesive. After the double-sided fragmentation process is completed, the protective film is removed.

8. The method for preparing the amorphous nanocrystalline shielding sheet according to claim 1, characterized in that: Before and during the double-sided fragmentation process, the process further includes: heating the rubber-coated soft magnetic composite strip; The heating temperature of the heating treatment is 40°C to 80°C.

9. The method for preparing the amorphous nanocrystalline shielding sheet according to claim 1, characterized in that: The double-sided adhesive in the adhesive-coated soft magnetic composite strip is in a molten state with fluidity; During the double-sided shredding process, the double-sided adhesive in a molten state is filled into the shredded gaps of the double-sided shredded tape material.

10. The method for preparing the amorphous nanocrystalline shielding sheet according to claim 1, characterized in that: The double-sided fragmentation process is performed at least once continuously.